2005
DOI: 10.2136/sssaj2004.0371
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Respiration and Organic Carbon Indicate Nutrient Cycling Recovery in Reclaimed Soils

Abstract: ent on a reclaimed area will depend to a large degree on a range of soil physical, chemical, and biological vari-Soil quality and the ability of soil to sustain nutrient cycling in drasables (National Research Council, 1994) and the severe tically disturbed ecosystems will influence the establishment and maintenance of a permanent and stable plant community. We undertook perturbations that occur in the strip mining process can research to evaluate a recently developed method to assess soil quality severely im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
51
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 43 publications
6
51
0
1
Order By: Relevance
“…However, it usually takes more than 20 years to restore a soil's microbial biomass to the level of the original landscape in the semi-arid mining areas in Wyoming, USA [49]. The correlation analysis revealed a highly significant positive correlation between the MBC and the SOC contents (r = 0.737, p < 0.01), which is in agreement with the results of Adeli et al [26] and Ingram et al [50]. This suggests that organic matter is the main energy source for soil microorganisms; the organic carbon added to reclaimed soils during agricultural activities is rapidly utilized by microbial communities, which contributes to the rapid increase in the soil's MBC content and the restoration of a damaged ecosystem.…”
Section: Discussionsupporting
confidence: 89%
“…However, it usually takes more than 20 years to restore a soil's microbial biomass to the level of the original landscape in the semi-arid mining areas in Wyoming, USA [49]. The correlation analysis revealed a highly significant positive correlation between the MBC and the SOC contents (r = 0.737, p < 0.01), which is in agreement with the results of Adeli et al [26] and Ingram et al [50]. This suggests that organic matter is the main energy source for soil microorganisms; the organic carbon added to reclaimed soils during agricultural activities is rapidly utilized by microbial communities, which contributes to the rapid increase in the soil's MBC content and the restoration of a damaged ecosystem.…”
Section: Discussionsupporting
confidence: 89%
“…We observed that though microbes from undisturbed soils contained less N than microbes from reclaimed communities, they took up N at a greater rate. This would seem to support a hypothesis that we put forward previously (Ingram et al, 2005) in which we suggested that there is a greater supply of labile material present in reclaimed soils despite lower overall concentrations of TN. In contrast, undisturbed soils have a greater mass of TN, but much of it is present in more humified soil organic matter (SOM) fractions, and this N is less available for microbial uptake.…”
Section: Discussionsupporting
confidence: 86%
“…The results of our current work though give rise to somewhat of a conundrum, in that TN is almost always lower in reclaimed soils (approximately 30% lower) but most of the time plant productivity is greater (74% of reclaimed sites averaged 77% greater production relative to undisturbed sites; Ingram et al, 2005 andL. Ingram, unpublished data, 2006).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…From 4 yr of sampling at four soil depths in a long-term integrated croplivestock trial on Typic Kanhapludults in Georgia, the association between net N mineralization during 24 d and the flush of CO 2 in 3 d was very strong (r 2 = 0.82; n = 646) (Franzluebbers and Stuedemann, 2008). From a range of reclaimed mine spoils and native grasslands in Wyoming, the association between net N mineralization during 21 d and the flush of CO 2 in 3 d was also strong (r 2 = 0.72; n = 22; Ingram et al, 2005). From Typic Kanhapludults in North Carolina, strong association of net N mineralization during 24 d with the flush of CO 2 in 3 d was observed, but with a plateau effect occurring when the flush of CO 2 exceeded 500 mg kg -1 (r 2 = 0.72; n = 120; Franzluebbers and Brock, 2007).…”
mentioning
confidence: 95%